2022
DOI: 10.1371/journal.pone.0270612
|View full text |Cite
|
Sign up to set email alerts
|

Award rate inequities in biomedical research

Abstract: Purpose The analysis of existing institutional research proposal databases can provide novel insights into science funding parity. The purpose of this study was to analyze the relationship between race/ethnicity and extramural research proposal and award rates across a medical school faculty and to determine whether there was evidence that researchers changed their submission strategies because of differential inequities across submission categories. Method The authors performed an analysis of 14,263 biomedi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Additional dynamics disadvantaging non-white PIs were found: Black/AA and Asian PIs revised and resubmitted applications more times than white PIs before getting funded, and Black/AA PIs were also less likely to revise and resubmit a new proposal after a failed attempt due to lower review scores ( Ginther et al, 2011 ; Hoppe et al, 2019 ; Ginther et al, 2016 ). Similarly, in a study of proposal submission patterns of faculty at a single medical school from 2010 to 2022, Black/AA PIs submitted 40% fewer R01 proposals than white PIs on a per-PI basis (Tables 1 and 4 from Zimmermann et al, 2022 ). Another study of both gender and race found that Black/AA and Asian women investigators were less likely to receive an R01 award than white women, highlighting a “double bind” for women of color ( Ginther et al, 2016 ).…”
Section: Discussionmentioning
confidence: 96%
“…Additional dynamics disadvantaging non-white PIs were found: Black/AA and Asian PIs revised and resubmitted applications more times than white PIs before getting funded, and Black/AA PIs were also less likely to revise and resubmit a new proposal after a failed attempt due to lower review scores ( Ginther et al, 2011 ; Hoppe et al, 2019 ; Ginther et al, 2016 ). Similarly, in a study of proposal submission patterns of faculty at a single medical school from 2010 to 2022, Black/AA PIs submitted 40% fewer R01 proposals than white PIs on a per-PI basis (Tables 1 and 4 from Zimmermann et al, 2022 ). Another study of both gender and race found that Black/AA and Asian women investigators were less likely to receive an R01 award than white women, highlighting a “double bind” for women of color ( Ginther et al, 2016 ).…”
Section: Discussionmentioning
confidence: 96%